2017
DOI: 10.1213/ane.0000000000002298
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Evaluating Burnout, Health Status, Depression, Reported Alcohol and Substance Use, and Social Support of Anesthesiologists

Abstract: Many anesthesiologists exhibit some high-risk burnout characteristics, and these are associated with lower mental health scores. Personal and professional support were associated with less emotional exhaustion, but overall burnout scores were associated with work satisfaction and professional support. Respondents were generally economically satisfied but also felt less in control at work and that their job kept them from friends and family. The association between burnout and substance use may not be as strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 29 publications
3
87
1
6
Order By: Relevance
“…The present study showed that the mean MCS score was significantly below the normative values, and nearly 30% of young doctors reported MCS scores that were 1 SD below the normative values. The results of a previous study using a 12-item Short Form Health Survey (SF-12) also reported that the mean mental composite score was 1 SD below the normative values [23] . A survey conducted in Malta also indicated that 49.4% of young doctors faced significant psychological distress [24] .…”
Section: Discussionmentioning
confidence: 92%
“…The present study showed that the mean MCS score was significantly below the normative values, and nearly 30% of young doctors reported MCS scores that were 1 SD below the normative values. The results of a previous study using a 12-item Short Form Health Survey (SF-12) also reported that the mean mental composite score was 1 SD below the normative values [23] . A survey conducted in Malta also indicated that 49.4% of young doctors faced significant psychological distress [24] .…”
Section: Discussionmentioning
confidence: 92%
“…A high SJL score may result from staying up late due to socialising: such time spent with social support, i.e. friends and other acquaintances, is considered a protective factor against burnout (Wittmann et al 2006;Śliwiński et al 2014;Woodhead et al 2014;Hyman et al 2017). However, this relationship requires further investigations, which should also encompass the negative effect of SJL on cardiometabolic profile (Rutters et al 2014).…”
Section: Hypotheses 1 Andmentioning
confidence: 99%
“…Burnout has been linked to factors associated with both the work environment and personal disposition. For example, high emotional intelligence, high agreeableness and low neuroticism were found to play a protective role (Rabatin et al 2016;van der Wal et al 2016;Lindeman et al 2017), while risky alcohol consumption, insomnia, alexithymia or poor general mental health are believed to be associated with a high risk of burnout (Pedersen et al 2016;Hyman et al 2017;Metlaine et al 2017). More precise identification of risk factors, or predictors, of burnout symptoms may facilitate more effective prophylaxis, early diagnosis and improved therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Operating rooms are highly stressful environments involving complex, respectful, and essential interactions. Surgeons, anesthesiologists and nurses can develop health problems, social issues and substance use due to stress and burnout 3,4 . Employee disengagement is estimated to cost around 450 billion USD per year, and illness-related absences are common in burned out employees 5 .…”
Section: Introductionmentioning
confidence: 99%